(untitled) (Journal of Hama University, 2026)
Work was done on adding niobium and manganese metals to the high-chromium white cast iron alloy from which excavator teeth and crusher hammers are made, with the aim of testing the resulting alloy in difficult applications. The most important chemical reactions that occur during smelting and the amounts of heat released from these reactions were explained, in addition to performing the necessary calculations for these additions to control The resulting proportions are according to what was planned. The results showed the combustion of a quantity of components due to smelting and the presence of multiple metal oxides within the slag. The calculations of the proportions of gases in the melt, especially nitrogen and oxygen, were improved. The calculations resulted in the reactions being spontaneous with a very small percentage of oxygen and the dissolution limit of nitrogen in the melt. As a result of the calculations, we identified the reactions, both spontaneous and non-spontaneous, and methods for activating and controlling them to obtain the specific chemical composition of the required alloy.